Evaluación del material polimérico clorhidrato de EUDRAGIT E-100 como potencial excipiente de liberación modificada de fármacos en matrices sólidas (2014)
The effect of the polymer system modified Clorhidrato Eudragit E-100, as modified release excipient potential on the dissolution profile of the drug model, 5H-dibenzo [b, f] azepine-5-carboxamide in aqueous media was determined and two systems buffer pH 1.2 and 7.4 with 0.15M ionic strength at 37 ° C temperature In this study were obtained validation parameters of the method for the quantification the drug such as: selectivity, repeatability, reproducibility and linearity. Also were performed previous studies for determining specific parameters for obtaining the tablets of the study. Among these are hardness, moisture adsorption capacity, diameter, thickness and disintegration time. Once these characteristics are determined, were evaluated dissolution profiles for the tablets of the study and reference, these tablets were composed of Clorhidrato de Eudragit E100 and microcrystalline cellulose pH 102, respectively, together with the model drug in proportions 1:1 polymer: drug. The data obtained were analyzed by a statistical analysis (ANOVA), which established one significant effect between the dissolution medium (buffer pH 1.2, aqueous medium and buffer pH 7.4) and polymeric system, on the dissolution percentage of the drug. This study concluded that the polymer system of study, no delay of release the drug, because is observed the behavior of an immediate release dosage form.